1977
DOI: 10.1002/ijc.2910190215
|View full text |Cite
|
Sign up to set email alerts
|

Mouse mammary tumor virus production stimulated by hormones and polyamines in cells grown in semi‐synthetic in vitro conditions

Abstract: Hormonal regulation of mouse mammary tumor virus (MMTV) synthesis was studied in the CCL-51-SF cell subline derived from the Sykes' mammary tumor cell line CCL-51 and adapted to grow in semi-synthetic in vitro conditions. The virus was quantitated by measuring the supernatant reverse transcriptase activity in exogenous reaction using poly (rA)-oligo (dT) and poly (rC)-oligo (dG) as template/primers. The cells produced a low but significant amount of virus in the absence of any hormones and serum proteins. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In agreement with previous in vitro studies, these observations demonstrate that glucocorticoid treatment in vivo increased MuMTV RNA in mammary tumors from a strain that contains the exogenous MuMTV-S. The effect of prolactin on the level of MuMTV RNA in the BALB/ cfC3H mammary tumors may be consistent with the report that prolactin increased MuMTV production in the presence of glucocorticoid hormones (33).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous in vitro studies, these observations demonstrate that glucocorticoid treatment in vivo increased MuMTV RNA in mammary tumors from a strain that contains the exogenous MuMTV-S. The effect of prolactin on the level of MuMTV RNA in the BALB/ cfC3H mammary tumors may be consistent with the report that prolactin increased MuMTV production in the presence of glucocorticoid hormones (33).…”
Section: Resultssupporting
confidence: 92%
“…Similarly, MuMTV RNA in hormone-induced BALB/c mammary tumor cells in vitro was increased by glucocorticoid treatment (13). Although prolactin alone had no effect on MuMTV production in C3H tumor cells in vitro (4, 12, 33), it is not clear whether prolactin in combination with glucocorticoids increased MuMTV production (4,33). Optimal MuMTV production in vitro by mammary cells from midpregnant BALB/cfC3H glands was dependent upon both prolactin and glucocorticoids (37).…”
mentioning
confidence: 99%
“…The effect of prolactin in stimulating the MTV RNA ecpression in vivo seems similar to the action of glucocorticoids in vitro (19,21). In in vitro studies no effect on the MTV RNA expression has been observed by the addition of prolactin alone (19), but prolactin increased the MTV RNA expression in combination with dexamethasone and insulin (24).…”
Section: Resultsmentioning
confidence: 92%
“…The peptide hormone prolactin has been shown to enhance the effects of glucocorticoids on the expression of MMTV (Svec & Links, 1977). More recently it has been shown that prolactin at physiological concentrations may play a greater role in the control of MMTV expression in vivo than previously thought, particularly in parous mice (Munoz & Bolander, 1989).…”
Section: Prolactinmentioning
confidence: 99%